2014
DOI: 10.1007/s00296-014-2945-y
|View full text |Cite
|
Sign up to set email alerts
|

Serious infections in patients with rheumatoid arthritis and other immune-mediated connective tissue diseases exposed to anti-TNF or rituximab: data from the Spanish registry BIOBADASER 2.0

Abstract: Data on infections in patients exposed to biologic therapies are mainly focused on rheumatoid arthritis (RA). Little is known about the safety profile in other immune-mediated connective tissue diseases (ICTD). The purpose of this study was to describe and to compare the risk of serious infections (SI) in patients with RA and other ICTD on anti-TNF or rituximab and to identify predictors of SI. We analyzed RA or other ICTD patients on anti-TNF or rituximab included in the Spanish registry BIOBADASER 2.0 (2000-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 23 publications
8
26
1
2
Order By: Relevance
“…One study comparing bDMARDs with the general population reported standardised incidence rates of 16–20 for tumour necrosis factor-α inhibitor (TNFi) and even higher for RTX (table 1). 15 In total, six studies,21 44–48 performed in European and American datasets, of which four were at low risk of bias, focused on the occurrence of herpes zoster, most of them reporting no increased risk for this type of infection in patients on TNFi (no studies for other bDMARDs), particularly the studies at low risk of bias and/or those that had been adjusted for dropouts 21 44–46…”
Section: Resultsmentioning
confidence: 99%
“…One study comparing bDMARDs with the general population reported standardised incidence rates of 16–20 for tumour necrosis factor-α inhibitor (TNFi) and even higher for RTX (table 1). 15 In total, six studies,21 44–48 performed in European and American datasets, of which four were at low risk of bias, focused on the occurrence of herpes zoster, most of them reporting no increased risk for this type of infection in patients on TNFi (no studies for other bDMARDs), particularly the studies at low risk of bias and/or those that had been adjusted for dropouts 21 44–46…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the potential influence of anti-TNF- α -based therapy on the setting of adaptive immune functional responses against viral and bacterial antigens, previous reports in different inflammatory diseases, including psoriasis and psoriatic arthritis, rheumatoid arthritis, spondyloarthritis, and Crohn's disease, showed that most common adverse events are represented by the occurrence of infections and by an unexpected high frequency of reactivation of latent tuberculosis infections (LTB), which are often severe and characterized by extrapulmonary and disseminated lesions [58]. …”
Section: Discussionmentioning
confidence: 99%
“…Coadministration of biological factors or a combination of these therapies with high doses of corticosteroids multiplies the risk of infection and should definitively be avoided, especially in elderly patients with lung comorbidities. On the other hand, upon a developed lung infection, discontinuation of immunosuppression does not lead to precipitous reconstitution of the immune system [55,65,66,67,68,69,70,71]. All the above parameters significantly increase the risk of bacterial, mycobacterial, viral, and fungal pulmonary infections in CTD patients (fig.…”
Section: Acute Lung Infections In Ctdsmentioning
confidence: 99%